Design factors influencing consumer acceptance in cultural and creative products: an integrated review - Jia, Zhao; Md Ishak, Siti Mastura; Yahaya, Mohd Faiz (Human Resources Management Academic Research Society (HRMARS), 2024)
With the development of the global economy and the increasing prosperity of culture, the demands of consumer for cultural factors in cultural and creative products has changed and put forward higher requirements. But the current design quality of cultural and creative product is not yet able to meet the needs of modern consumers. This paper aims to review the main findings of previous articles on the relationship between design factors and consumer acceptance of cultural and creative products, and to form three independent themes through comprehensive analysis: Cultural elements that enhance the design value of cultural and creative products. Modern design innovation of cultural and creative products. Consumers' emotional experience in cultural and creative products. By applying the "literature review synthesis process", this paper conducts a cross-analysis, integrates the possibilities, and prioritizes the synthesis of information in order to improve the design quality of cultural and creative products for better consumer acceptance. The results of the study contribute to the development of a theoretical framework to enhance consumer acceptance by clearly and creatively displaying cultural features and emotional experience elements in cultural creative products, balancing product aesthetics and creativity with practicality and product quality. Finally, suggestions are made for future research directions.